University, knowledge, and pandemic: Knowledge management as a university basis for overcoming crises - Estevão Romeiro, Artieres; Weingärtner Reis, Ingrid (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Universities are recognized as spaces for the generation and management of knowledge for innovation and improvement of productive environments and social life. With the Covid-19 pandemic, universities have been put to the test, both for the resolution of the health crisis and for the pedagogical organization in the digital context. Based on a critical dialectical analysis, of a philosophical and expectational order, the article aims to identify categories of knowledge management in universities. The results show the elements of institutional organization common to university environments that favor adaptation to complex scenarios.